Działalność nieewidencjonowana małoletnich a prawa konsumentów - Urban, Agnieszka (Studia Prawa Publicznego, 2025)
A non-registered activity can be pursued by both adults and minors, on condition that the income from this activity does not exceed the limit introduced by the law in force. At the time of writing, this was 75% of the minimum wage. When verifying the limit, it is essential to keep a sales registry to help control the income. If the limit is exceeded, the non-registered activity in question is deemed to constitute business activity and, consequently, the obligation to register the activity in the CEIDG arises. Unregistered business activity consists in the performance of activities which, in their effect, would not fulfil the prerequisites of business activity. For natural persons, as long as the income limit is observed, this may be a preliminary form of conducting subsequent economic activity or a form of earning money for minors. An unregistered activity allows one to develop skills in running one’s own business, as well as to familiarise oneself with the various legal actions that are necessary to run such an activity.The purpose of this article is to establish the principles of unregistered activity by minors and also the public law and tax consequences that may arise from the unregistered activity of a person with limited legal capacity for themselves, but also for their legal representatives, and consumers.